2005
DOI: 10.1227/01.neu.0000156202.80185.32
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome in Rheumatoid Ranawat Class IIIb Myelopathy

Abstract: A large subset of patients with CVJ rheumatoid myelopathy may reach Class IIIb. These patients have unique management considerations. Surgery (despite high morbidity) often remains the best therapeutic option available to them. Improvement of even one grade in their Ranawat score from Class IIIb to Class IIIa brought about by surgery confers on them a significant benefit in terms of their quality of life and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 35 publications
1
26
0
2
Order By: Relevance
“…To our knowledge, there have been only 2 studies that included analyses of type of spine surgery (anterior vs posterior) in RA patients. 7,30 Casey et al 7 reported the results of a prospective study involving 116 patients with vertical translocation, a Ranawat neurological classification of at least Class II, and a mean postoperative follow-up of 62.3 months. The choice of anterior-posterior combination vs posterior-only surgery was made based on whether the compression was predominantly anterior or posterior and if the translocation was reducible with traction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, there have been only 2 studies that included analyses of type of spine surgery (anterior vs posterior) in RA patients. 7,30 Casey et al 7 reported the results of a prospective study involving 116 patients with vertical translocation, a Ranawat neurological classification of at least Class II, and a mean postoperative follow-up of 62.3 months. The choice of anterior-posterior combination vs posterior-only surgery was made based on whether the compression was predominantly anterior or posterior and if the translocation was reducible with traction.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, the authors also showed higher incidence of chest infection in the anterior-approach group, but the association was not statistically significant. Nannapaneni and colleagues 30 examined surgical outcome in patients with very poor preoperative neurological status (Ranawat Class IIIB) and a mean follow-up of 39 months. All the patients underwent halo placement before surgery, and if their subluxation was reducible, they had the posterioronly surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding those subjects with advanced functional impairment (ranawat IIIA and IIIB), Casey, et al published an important study where they suggest that surgical treatment for terminal patients and patients with advanced disease is related to higher rates of morbimortality and a poor perspective for functional recovery [21]. On the other hand, Nannapaneni, et al reported results for different types of treatment in those patients with advanced disease and showed that, with surgical treatment, 60% of them were capable of ambulating again and all of them experienced some level of cervical pain relief and quality of life improvement [22]. In this way, the answer to those dilemmas is not clear yet, and one must take into ac-restricting an average of 30° of flexoextension, and 35° to 40° of neck lateral rotation [29].…”
Section: Principles and Controversies In The Treatment Of Rheumatoid mentioning
confidence: 99%
“…При разрушении зубовидного отростка может развиться задний АтА-подвывих. Прогрессирующая воспалительная деструк-ция боковых масс атланта и хроническая кра-ниоцервикальная нестабильность приводят к вертикальному смещению (краниальное расположение, базилярное внедрение или верхняя миграция) зубовидного отростка [14][15][16]. Зубовидный отросток движется к foramen magnum затылочной кости и за пре-делы ее границ.…”
unclassified